Renal cell carcinoma in a cow - Zabid Yener (Eurasian Journal of Veterinary Sciences)
A case of renal cell carcinoma in a 11 years old cow was descnbed. Grossly, whitish-grey coloured, 1-2 cm in diameter and well-circumscribed masses were seen in the cortex and medulla of one lobule of the right kidney Tumour was primarily cortical, and extended into the renal calix. Microscopically tumour was diagnosed as renal cell carcinoma.